Lipid Metabolism of Manganese-deficient Algae: I. Effect of Manganese Deficiency on the Greening and the Lipid Composition of Euglena Gracilis Z - Constantopoulos, George (1970)
The growth of photoautotrophic Euglena gracilis Z is strongly inhibited by manganese deficiency, whereas chlorophyll formation is not appreciably affected. The galactosyldiglyceride content of the manganese-deficient photo-autotrophic Euglena was about 40% lower on the basis of either chlorophyll content or dry weight. When dark-grown cultures of Euglena were grown photoheterotrophically in light sufficient for the greening of the cells, or photosynthesis, manganese deficiency resulted in a reduction of the cellular content of chlorophyll and galactosyldiglycerides to 40% of control values, indicating interference with chloroplast formation. The fatty acids of the photoheterotrophic manganese-deficient cells were mainly saturated, with an unusual accumulation (about 45%) of the total fatty acids) of myristic acid. In spite of this, the galactosyldiglycerides contain mainly unsaturated fatty acids. Ninety per cent of the fatty acids of the monogalactosyldiglyceride are unsaturated, including large amounts of α-linolenic acid. The ratio of chlorophyll to galactosyldiglyceride content of the cells was remarkably constant at all manganese deficiency levels.